2009
DOI: 10.1016/s1808-8694(15)30782-5
|View full text |Cite
|
Sign up to set email alerts
|

Facial paralysis associated with acute otitis media

Abstract: The paralysis was of sudden onset in 95% of the cases. Recovery was of 85% for grade I (House-Brackman) and 15% for grade II (House-Brackman). Treatment was clinical, with antibiotics and steroids - yielding good results. In those patients with electrical bad prognosis, facial nerve decompression turned their evolution into a favorable one.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 10 publications
1
20
0
Order By: Relevance
“…9 Because corticosteroid agents remain the best treatment for inflammatory, virally induced, immunemediated disease, we advocate their use unless contraindicated by another comorbid condition.…”
Section: Managementmentioning
confidence: 99%
“…9 Because corticosteroid agents remain the best treatment for inflammatory, virally induced, immunemediated disease, we advocate their use unless contraindicated by another comorbid condition.…”
Section: Managementmentioning
confidence: 99%
“…Systemic antibiotic therapy and systemic steroids were used, and the treatment was a success. In some cases, facial nerve decompression treatment is necessary due to unsuccessful antibiotic and steroid treatment [6,10]. In our case no facial nerve decompression treatment was needed.…”
Section: Discussionmentioning
confidence: 73%
“…Facial paralysis is a very rare complication of AOM (seen in about 1–4% of cases), and antibiotic application decreases the appearance of facial paralysis [10]. Duman et al, Viola et al, and Patigaroo et al reported ecthyma gangrenosum and AOM or externa with facial nerve palsy in healthy infants [9,11,12].…”
Section: Discussionmentioning
confidence: 99%
“…However, a few patients may need surgical interventions likemyringotomywith or without ventilation tube insertion. Myringotomycan eliminate the middle ear fluid, butcortical mastoidectomy, with or without facial nerve decompression,could be considered in few cases to control this disorder.Total facial nerve paralysis(HB Grade 6), total axonal degeneration, or poor axonal regeneration rates as determined by electrophysiological studies are the indications for facial nerve decompression surgeries.Decompression surgery may be more effective when the operation is performed within 3 weeksafter the onset of FNP [12]. None of our patients needed any of these procedures because of the benign courses of their facial paralysis.…”
Section: Discussionmentioning
confidence: 92%
“…The consensus among most authors on facial nerve paralysis with acute otitis media is to use conservative treatment approaches. Broad-spectrum intravenous antibiotics must be considered as a first step [12]. Intravenously applied maximum dosage antibiotherapy may assure control of the infectious process and stop the bacterial proliferation.…”
Section: Discussionmentioning
confidence: 99%